Expandable polystyrene containing expandable graphite and preparation method thereof

By modifying the expandable graphite with epoxidized styrene-butadiene block copolymer and adding it to the emitable polystyrene material, the problem that traditional polystyrene foaming materials are difficult to take into account between flame retardant properties and mechanical properties, and efficient flame retardant and mechanical properties are achieved.

CN118878999BActive Publication Date: 2025-03-04TIANJIN JIATAI WEIYE CHEM IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411396854.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-03-04
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

Traditional polystyrene foaming materials are difficult to balance the flame retardant properties and mechanical properties, especially after the addition of expandable graphite, the uniform dispersion and flame retardant effects of the materials are limited.

Method used

The expandable graphite is modified by using epoxidized styrene-butadiene block copolymer to form modified expandable graphite and added to the emitable polystyrene material, and the binding force with the polymer substrate is enhanced by bridging of the modified carbon material.

Benefits of technology

It is achieved to maintain good flame retardant effect and mechanical properties under a small amount of addition, including the improvement of thermal conductivity, bending strength, tensile retention rate and ultimate oxygen index.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to the field of foaming materials, in particular to an expandable polystyrene containing expandable graphite and a preparation method thereof. An expandable polystyrene containing expandable graphite comprises the following raw materials in parts by weight: 80-100 parts of a polymer substrate, 1-8 parts of a liquid material, 0.1-1 parts of a coating agent, 5-30 parts of a modified carbon material, 1-3 parts of a nucleating agent, 0.5-1 parts of a plasticizer, and 0.5-1 parts of a stabilizer; the modified carbon material is prepared by modifying a carbon material with an epoxidized styrene-butadiene block copolymer. The thermal conductivity of the obtained expandable polystyrene material is ≤0.033 W / m•K, the bending strength can reach 2.90-3.26MPa, the tensile retention rate can reach 80.0-90.8%, and the limiting oxygen index can reach 35.1-38.7%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of foaming materials, and in particular to an expandable polystyrene containing expandable graphite and a preparation method thereof. Background Art

[0002] Polystyrene (EPS) is widely used in various occasions due to its light texture, low cost, and the ability to be formed by steam heating. For example, it is used to make building insulation boards or daily necessities such as lunch boxes and packaging bags. However, in recent years, with the rapid development of the industry and the increasing diversification of market demand, the application field of polystyrene has also been expanded. Traditional polystyrene with only a single performance has gradually failed to meet people's production and living needs. Polystyrene needs to continue to develop in the direction of multi-function and high performance.

[0003] At present, in the field of flame retardant expandable polystyrene, according to the type of flame retardant, it can be divided into two categories: halogen-containing flame retardant products and halogen-free flame retardant products. Halogen-containing flame retardant products are facing the risk of being restricted in use because the halogen gas released by their flame retardants when burning has certain toxicity. Most halogen-free flame retardant products use inorganic flame retardant series, in which graphite and carbon black added to polystyrene foaming materials can fundamentally eliminate the hidden danger of polystyrene ignition.

[0004] In view of the above-mentioned related technologies, the applicant found that after grinding, expandable graphite is difficult to be evenly dispersed in the polymer in suspension polymerization, and the acidic groups inevitably introduced during the production process affect the chain growth process of the polymerization process, resulting in abnormalities in the local polymerization branching degree and polymerization degree, so that the product cannot be used for normal foaming in a foaming machine. Therefore, it is necessary to introduce other inorganic powders such as aluminum hydroxide or phosphorus compounds to provide additional flame retardancy for the product. This will reduce the mechanical properties due to the excessive introduction of inorganic flame retardants. Summary of the invention

[0005] In order to improve the flame retardant properties of expandable polystyrene while ensuring its mechanical properties, the present application provides an expandable polystyrene containing expandable graphite and a preparation method thereof.

[0006] In a first aspect, the present application provides an expandable polystyrene containing expandable graphite, which adopts the following technical solution.

[0007] An expandable polystyrene containing expandable graphite comprises the following raw materials in parts by weight: 80-100 parts of a polymer substrate, 1-8 parts of a liquid material, 0.1-1 parts of a coating agent, 5-30 parts of a modified carbon material, 1-3 parts of a nucleating agent, 0.5-1 parts of a plasticizer, and 0.5-1 parts of a stabilizer;

[0008] The modified carbon material is prepared by modifying the carbon material with an epoxidized styrene-butadiene block copolymer.

[0009] In some embodiments, the carbon material may be one or more of expandable graphite, multi-arm carbon nanotubes, natural flake graphite, and chopped graphene.

[0010] By adopting the above technical scheme, taking the carbon material as expandable graphite as an example, the present application adds modified expandable graphite to the expandable polystyrene material. When the expandable polystyrene material encounters high temperature, the intercalation compound in the expandable graphite begins to decompose, generating a large amount of gas, causing the graphite layer to expand rapidly along the C-axis direction to form a worm-like expandable graphite. The expanded graphite layer forms a dense protective layer to isolate the fire source from the expandable polystyrene material body to prevent the further spread of the fire. The expandable graphite can also promote the carbonization reaction of the expandable polystyrene material at high temperature to form a dense carbon layer. This carbon layer not only has the effect of heat insulation and oxygen isolation, but also can further hinder the spread of the fire. In addition, the flat multilayer structure and fine particle size characteristics of the expandable graphite enable it to produce an energy absorption effect during the fracture process, thereby improving the impact strength and compression strength of the expandable polystyrene material and improving the corrosion resistance and chemical resistance of the foamable material.

[0011] The expandable graphite is modified by using epoxidized styrene-butadiene block copolymer, the polystyrene block is compatible with the polymer substrate, the polybutadiene block is compatible with the expandable graphite, a microphase separation structure is formed, the interfacial compatibility is improved, the expandable graphite is uniformly dispersed in the polymer substrate, and the expandable graphite is prevented from agglomerating, so that the product can be smoothly used for normal foaming machine foaming. In addition, the epoxy group on the epoxidized styrene-butadiene block copolymer can react with the polymer substrate, further improving the binding property of the epoxidized styrene-butadiene block copolymer with the polymer substrate. The epoxidized styrene-butadiene block copolymer plays a bridging role between the expandable graphite and the polymer substrate, improving the binding force of the expandable graphite with the polymer substrate, so that the expandable graphite fully and comprehensively exerts its flame retardant effect, and still maintains a good flame retardant effect in a small amount without adding a flame retardant, and the mechanical properties will not be significantly reduced.

[0012] In some embodiments, the nucleating agent is at least one of polyethylene wax, titanium dioxide, talcum powder, polytetrafluoroethylene powder, and an organic amine nucleating agent.

[0013] In some embodiments, the plasticizer is at least one of dimethyl phthalate, diethyl phthalate, and dibutyl phthalate.

[0014] Furthermore, the preparation method of the epoxidized styrene-butadiene block copolymer is:

[0015] 1) Living anionic polymerization

[0016] Add styrene monomer into an inert solvent, control the reaction temperature to -78 -0°C, and carry out living anionic polymerization under the initiation of n-butyl lithium to obtain active polystyrene chain segments;

[0017] 2) Chain transfer reaction

[0018] Divinylbenzene is used as a chain transfer agent to react with the active polystyrene chain segments to form a block structure;

[0019] 3) Second monomer polymerization

[0020] Step 2) The obtained block structure reacts with butadiene monomer to carry out the second stage polymerization reaction.

[0021] The butadiene monomer is polymerized on the active polystyrene chain segment to form a block copolymer;

[0022] 4) Termination of the reaction

[0023] Using a terminator to terminate the polymerization reaction to form a styrene-butadiene block copolymer;

[0024] 5) Maleic anhydride grafting

[0025] The block copolymer obtained in step 4) is subjected to a grafting reaction with maleic anhydride in the presence of dibenzoyl peroxide to obtain a maleic anhydride-styrene-butadiene block copolymer;

[0026] 6) Epoxidation reaction

[0027] The maleic anhydride-block copolymer is reacted with epichlorohydrin under alkaline conditions to obtain an epoxidized styrene-butadiene block copolymer;

[0028] 7) Post-processing:

[0029] Filter, wash and dry to remove unreacted monomers, solvents and impurities.

[0030] By adopting the above technical scheme, styrene and butadiene are first used as polymerization monomers to obtain a styrene-butadiene block copolymer, and then maleic anhydride is reacted with the styrene-butadiene block copolymer, and the double bonds of the maleic anhydride react with the butadiene segment to generate anhydride groups on the styrene-butadiene block copolymer; then the anhydride groups react with epichlorohydrin to generate epoxy groups, and an epoxidized styrene-butadiene block copolymer is obtained.

[0031] Furthermore, in step 1), the weight ratio of n-butyl lithium to styrene is (0.005-0.007):1, in step 2), the weight ratio of divinylbenzene to styrene is (0.003-0.004):1, and the weight ratio of styrene monomer to butadiene monomer is 1:(1.2-1.5).

[0032] Furthermore, the weight ratio of maleic anhydride to styrene is (0.05-0.07):1, and the weight ratio of epichlorohydrin to maleic anhydride is 1:(0.5-0.8).

[0033] By adopting the above technical scheme, adjusting the ratio of styrene monomer to butadiene monomer, and the amount of initiator and chain transfer agent, an epoxidized styrene-butadiene block copolymer with a specific structure is obtained. And adjusting the ratio of maleic anhydride to epichlorohydrin, adjusting the content of epoxy groups on the epoxidized styrene-butadiene block copolymer, an epoxidized styrene-butadiene block copolymer with a designed structure is obtained. The epoxidized styrene-butadiene block copolymer with this structure can fully play its role between the polymer substrate and the expandable graphite in the expandable polystyrene material. The expandable polystyrene with excellent comprehensive properties such as flame retardancy, mechanical properties and anti-corrosion properties is obtained.

[0034] Furthermore, the modified carbon material is modified expandable graphite, and the preparation method of the modified expandable graphite is:

[0035] At 60-120° C., the expandable graphite and the epoxidized styrene-butadiene block copolymer are subjected to a grafting reaction initiated by dibenzoyl peroxide to obtain modified expandable graphite;

[0036] The weight ratio of the epoxidized styrene-butadiene block copolymer to the expandable graphite is 1:(3-5).

[0037] Furthermore, the polymer substrate comprises general-grade polystyrene and foamed-grade polystyrene in a weight ratio of (3-5):1.

[0038] Furthermore, the weight ratio of the modified expandable graphite to the polymer substrate is 1:(12-18).

[0039] Furthermore, the average particle size of the expandable graphite is 30-50 nm.

[0040] By adopting the above technical solution, the modified expandable graphite has a uniform and dense network structure in the polymer matrix, providing all-round flame retardant protection.

[0041] In addition, during the granulation and extrusion process, the lamellar structure in the system will also disperse and slide, and the surface of the lamellar graphite can also interact with the long chain segments of the polymer material and disperse throughout the system. Within the ratio and particle size range specified in the present application, the lamellar graphite can not only promote the dispersion of the chain segment raw materials, but also the interaction between its corresponding charge structure and the polymer matrix significantly reduces the microphase separation in the system, thereby avoiding the penetration of chemical molecules / reagents in the system, and the corresponding chain segment action can make the system entanglement more dense, thereby enhancing the mechanical properties.

[0042] Furthermore, the liquid material is at least one of n-hexane, n-pentane, isopentane and n-butane.

[0043] In a second aspect, the present application provides a method for preparing expandable polystyrene containing expandable graphite, using the following technical solution.

[0044] A method for preparing expandable polystyrene containing expandable graphite comprises the following steps:

[0045] S1. The raw materials other than the coating agent are mixed, stirred, and then melt-blended to obtain a melt;

[0046] S2. granulating the melt, centrifugally drying, and sieving;

[0047] S3. After screening, the product is coated with a coating agent, and the product is filled and packaged.

[0048] In summary, this application has the following beneficial effects:

[0049] This application uses epoxidized styrene-butadiene block copolymer as a modifier to modify the carbon material, and then adds the modified carbon material to the foamable polystyrene material. The epoxidized styrene-butadiene block copolymer plays a bridging role between the carbon material and the polymer substrate, improves the bonding force between the carbon material and the polymer substrate, and enables the carbon material to fully exert its flame retardant effect. In the case of a small addition amount and without the addition of flame retardants, it still maintains a good flame retardant effect, and the mechanical properties will not be significantly reduced. The thermal conductivity of the obtained foamable polystyrene material is ≤0.033 W / m•K, the bending strength can reach 2.90-3.26MPa, the tensile retention rate can reach 80.0-90.8%, and the limiting oxygen index can reach 35.1-38.7%. DETAILED DESCRIPTION

[0050] The present application is further described in detail below with reference to the embodiments.

[0051] Raw materials and intermediate preparation examples

[0052] raw material

[0053] The raw materials in the examples of this application can be obtained from the market:

[0054] Coating agent, monoglyceride;

[0055] Nucleating agent, N,N-dimethyl-1,3-propylenediamine;

[0056] Plasticizer, dibutyl phthalate;

[0057] Stabilizer, methyl (2S)-2-amino-4-methylthiobutyrate;

[0058] Styrene, analytical grade;

[0059] n-Butyl lithium, analytical grade;

[0060] Divinylbenzene, analytical grade;

[0061] Butadiene, analytical grade;

[0062] Terminator, methanol;

[0063] Maleic anhydride, analytical grade;

[0064] Epichlorohydrin, analytical grade.

[0065] Preparation Example

[0066] Preparation Example I-1 to Preparation Example I-8

[0067] An epoxidized styrene-butadiene block copolymer, the preparation method of which is as follows:

[0068] 1) Living anionic polymerization

[0069] According to the raw material ratio in Table 1, styrene monomer was added to the inert solvent tetrahydrofuran, the reaction temperature was controlled to be -50°C, and a living anionic polymerization reaction was carried out under the initiation of n-butyl lithium. The reaction was carried out for 18 hours to obtain a living polystyrene segment;

[0070] 2) Chain transfer reaction

[0071] Divinylbenzene is used as a chain transfer agent to react with the active polystyrene chain segments to form a block structure;

[0072] 3) Second monomer polymerization

[0073] Step 2) the obtained block structure reacts with butadiene monomer to carry out a second stage polymerization reaction for 30 hours, so that the butadiene monomer is polymerized on the active polystyrene chain segment to form a block copolymer;

[0074] 4) Termination of the reaction

[0075] Using a terminator to terminate the polymerization reaction to form a styrene-butadiene block copolymer;

[0076] 5) Maleic anhydride grafting

[0077] At 100° C., in tetrahydrofuran solvent, the block copolymer obtained in step 4) is subjected to a grafting reaction with maleic anhydride in the presence of dibenzoyl peroxide for 16 hours to obtain a maleic anhydride-styrene-butadiene block copolymer;

[0078] 6) Epoxidation reaction

[0079] The maleic anhydride-block copolymer is reacted with epichlorohydrin under alkaline conditions to obtain an epoxidized styrene-butadiene block copolymer;

[0080] 7) Post-processing:

[0081] Filter, wash and dry to remove unreacted monomers, solvents and impurities.

[0082] Table 1 Raw material ratio of epoxidized styrene-butadiene block copolymer (kg)

[0083]

[0084] Preparation Example I-9

[0085] A styrene-butadiene block copolymer, the preparation method of which is as follows:

[0086] 1) Living anionic polymerization

[0087] According to the raw material ratio of Preparation Example I-1 in Table 1, styrene monomer is added to an inert solvent, the reaction temperature is controlled to be -78-0°C, and a living anionic polymerization reaction is carried out under the initiation of n-butyl lithium to obtain a living polystyrene segment;

[0088] 2) Chain transfer reaction

[0089] Divinylbenzene is used as a chain transfer agent to react with the active polystyrene chain segments to form a block structure;

[0090] 3) Second monomer polymerization

[0091] Step 2) The obtained block structure reacts with butadiene monomer to carry out the second stage polymerization reaction.

[0092] The butadiene monomer is polymerized on the active polystyrene chain segment to form a block copolymer;

[0093] 4) Termination of the reaction

[0094] Using a terminator to terminate the polymerization reaction to form a styrene-butadiene block copolymer;

[0095] 5) Post-processing:

[0096] Filter, wash and dry to remove unreacted monomers, solvents and impurities.

[0097] Preparation Example II-1

[0098] A modified expandable graphite, the preparation method of which is:

[0099] At 100° C., in an inert solvent of tetrahydrofuran, 1 kg of expandable graphite and 3 kg of the epoxidized styrene-butadiene block copolymer from Preparation Example I-1 were subjected to a grafting reaction initiated by 0.003 dibenzoyl peroxide for 18 hours to obtain modified expandable graphite.

[0100] Preparation Example II-2

[0101] Different from Preparation Example II-1, the amount of the epoxidized styrene-butadiene block copolymer in Preparation Example II-2 was 5 kg.

[0102] Preparation Examples II-3 to II-9

[0103] Different from Preparation Example II-1, the epoxidized styrene-butadiene block copolymers in Preparation Examples II-3 to II-9 are from Preparation Examples I-2 to I-8, respectively.

[0104] Preparation Example II-10

[0105] Different from Preparation Example II-1, in Preparation Example II-10, the epoxidized styrene-butadiene block copolymer was replaced by the styrene-butadiene block copolymer from Preparation Example II-9. Example

[0106] An expandable polystyrene containing expandable graphite, and its preparation method is:

[0107] S1. According to the raw material ratio in Table 2, the raw materials other than the coating agent are mixed, stirred evenly, and transported to the melt pump. After the mixture is melted, the impurities are filtered out by the screen changer to obtain a melt;

[0108] S2. The melt is input into a granulator for granulation and cutting, centrifugal drying, and then sieving by a sieving machine; wherein the granulation is divided into 6 heating zones in sequence, and the temperatures are 160°C, 170°C, 190°C, 195°C, 200°C, and 190°C respectively;

[0109] S3. After screening, the product is coated with a coating agent, and the product is filled and packaged.

[0110] Table 2 Raw material ratio table of Examples 1-5 (kg)

[0111]

[0112] The polymer matrix includes general-grade polystyrene and foamed polystyrene in a weight ratio of 3:1; the liquid material is n-pentane; the modified carbon material is modified expandable graphite, which comes from Preparation Example II-1; and the average particle size of the expandable graphite is 40 nm.

[0113] Embodiment 6-8

[0114] Different from Example 2, the average particle sizes of expandable graphite in Examples 6-8 are 30 nm, 50 nm, and 20 nm, respectively.

[0115] Examples 9-17

[0116] Different from Example 2, the modified expandable graphite in Examples 9-17 comes from Preparation Examples II-2 to II-10, respectively.

[0117] Embodiment 18

[0118] Different from Example 2, the polymer substrate in Example 18 includes general-grade polystyrene and foamed-grade polystyrene in a weight ratio of 5:1.

[0119] Embodiment 19

[0120] Different from Example 2, the polymer substrate in Example 19 is foam-grade polystyrene.

[0121] Embodiment 20

[0122] Unlike Example 2, in Example 20, natural flake graphite is used to replace expandable graphite.

[0123] Comparative Example

[0124] Comparative Example 1

[0125] Different from Example 1, in Comparative Example 1, an equal amount of expandable graphite is used to replace the modified expandable graphite.

[0126] Comparative Example 2

[0127] Different from Example 1, the amount of modified expandable graphite used in Comparative Example 2 is 15 kg.

[0128] Performance Testing

[0129] The expandable polystyrene containing expandable graphite obtained in the examples and comparative examples was subjected to the following performance tests. The test results are shown in Table 3.

[0130] Thermal conductivity: a standard sample (300 mm × 300 mm × 50 mm) was prepared according to GB / T 10294-2008, and its thermal conductivity (unit: W / m•K) was tested. Ten samples were tested for each embodiment and comparative example, and the average value was recorded.

[0131] Bending strength: a standard specimen (120 mm × 25 mm × 20 mm) was prepared according to GB / T 8812.1-2007, and its bending strength (unit: MPa) was tested using a bending tester. Ten specimens were tested for each embodiment and comparative example, and the average value was recorded.

[0132] Acid and alkali resistance: The foamable materials obtained in the above embodiments and comparative examples were soaked in 10wt% sulfuric acid solution and 10wt% sodium hydroxide at 85°C for 8h, and then taken out. The elongation at break was tested according to GB1040-92 standard, and the retention rate of the elongation at break was calculated compared with the foamable material without acid soaking. The retention rate was calculated as follows: elongation at break after soaking / elongation at break without soaking × 100. Ten samples were tested for each embodiment and comparative example, and the average value of the values ​​was recorded;

[0133] Limiting oxygen index: The foamable materials obtained in the examples and comparative examples are made into polystyrene foam specimens with dimensions of (80±2) mm in length×(10±0.5) mm in width×(4±0.25) mm in thickness, and then tested in accordance with GB / T2406.2-2009 "Determination of Combustion Behavior of Plastics by Oxygen Index Method Part 2: Room Temperature Test". Ten specimens are tested for each example and comparative example, and the average value of the values ​​is recorded.

[0134] Table 3 Performance test results

[0135]

[0136] Combining Examples 1-20 with Comparative Examples 1-3 and Table 3, it can be seen that the thermal conductivity, bending strength, tensile retention rate after acid-base treatment and limiting oxygen index of the foamed materials obtained in Examples 1-20 are better than those of Comparative Examples 1-3, which indicates that the foamed materials prepared in the present application have better comprehensive properties such as flame retardancy, mechanical properties and corrosion resistance.

[0137] In combination with Examples 1-8, and in combination with Table 3, it can be seen that the particle size of the modified expandable graphite and the ratio with the polymer substrate will affect the overall performance of the foaming material, among which the ratio in Example 2 is the best. This may be because within the ratio and particle size range specified in the present application, the lamellar graphite can not only promote the dispersion of the segment raw materials, but also the interaction between its corresponding charge structure and the polymer matrix significantly reduces the microphase separation in the system, thereby avoiding the penetration of chemical molecules / reagents in the system, and the corresponding segment effect can make the system entanglement more dense, thereby enhancing the mechanical properties, and the modified expandable graphite has a uniform and dense network structure in the polymer substrate, providing flame retardant protection in all directions.

[0138] In combination with Example 2 and Example 9-17, and in combination with Table 3, it can be seen that the difference in the modifier modified by the expandable graphite will also affect the overall performance of the foam material. This may be because the ratio of styrene monomer to butadiene monomer, the proportion of maleic anhydride to epichlorohydrin are adjusted to obtain the epoxidized styrene-butadiene block copolymer of the designed structure. The epoxidized styrene-butadiene block copolymer of this structure can fully play a role between the polymer substrate and the expandable graphite in the expandable polystyrene material. Expandable polystyrene with excellent comprehensive properties such as flame retardancy, mechanical properties and anticorrosive properties is obtained.

[0139] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. An expandable polystyrene containing expandable graphite, characterized in that: The invention comprises the following raw materials in parts by weight: 80-100 parts of polymer substrate, 1-8 parts of liquid material, 0.1-1 parts of coating agent, 5-7.5 parts of modified expandable graphite, 1-3 parts of nucleating agent, 0.5-1 parts of plasticizer and 0.5-1 parts of stabilizer; The modified expandable graphite is prepared by modifying a carbon material with an epoxidized styrene-butadiene block copolymer; The preparation method of the epoxidized styrene-butadiene block copolymer is: 1) Living anionic polymerization Add styrene monomer into an inert solvent, control the reaction temperature to -78 -0°C, and carry out living anionic polymerization under the initiation of n-butyl lithium to obtain active polystyrene chain segments; The weight ratio of n-butyl lithium to styrene is (0.005-0.007): 1; 2) Chain transfer reaction Divinylbenzene is used as a chain transfer agent to react with the active polystyrene chain segments to form a block structure; The weight ratio of divinylbenzene to styrene is (0.003-0.004):1; 3) Second monomer polymerization Step 2) The obtained block structure reacts with butadiene monomer to carry out the second stage polymerization reaction. The butadiene monomer is polymerized on the active polystyrene chain segment to form a block copolymer; The weight ratio of styrene monomer to butadiene monomer is 1:(1.2-1.5) 4) Termination of the reaction Using a terminator to terminate the polymerization reaction to form a styrene-butadiene block copolymer; 5) Maleic anhydride grafting The block copolymer obtained in step 4) is subjected to a grafting reaction with maleic anhydride in the presence of dibenzoyl peroxide to obtain a maleic anhydride-styrene-butadiene block copolymer; The weight ratio of maleic anhydride to styrene is (0.05-0.07):1; 6) Epoxidation reaction The maleic anhydride-block copolymer is reacted with epichlorohydrin under alkaline conditions to obtain an epoxidized styrene-butadiene block copolymer; The weight ratio of epichlorohydrin to maleic anhydride is 1:(0.5-0.8); 7) Post-processing: Filter, wash and dry to remove unreacted monomers, solvents and impurities.

2. The expandable polystyrene containing expandable graphite according to claim 1, characterized in that: The preparation method of the modified expandable graphite is: At 60-120° C., the expandable graphite and the epoxidized styrene-butadiene block copolymer are subjected to a grafting reaction under the initiation of dibenzoyl peroxide to obtain modified expandable graphite; The weight ratio of the epoxidized styrene-butadiene block copolymer to the expandable graphite is 1:(3-5).

3. The expandable polystyrene containing expandable graphite according to claim 1, characterized in that: The polymer substrate includes general-grade polystyrene and foamed-grade polystyrene in a weight ratio of (3-5):

1.

4. The expandable polystyrene containing expandable graphite according to claim 2, characterized in that: The weight ratio of the modified expandable graphite to the polymer substrate is 1:(12-18).

5. The expandable polystyrene containing expandable graphite according to claim 1, characterized in that: The average particle size of the expandable graphite is 30-50 nm.

6. The expandable polystyrene containing expandable graphite according to claim 1, characterized in that: The liquid material is at least one of n-hexane, n-pentane, isopentane and n-butane.

7. A method for preparing expandable polystyrene containing expandable graphite according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. The raw materials other than the coating agent are mixed, stirred, and then melt-blended to obtain a melt; S2. granulating the melt, centrifugally drying, and sieving; S3. After screening, the product is coated with a coating agent, and the product is filled and packaged.

Citation Information

Patent Citations

  • Extruded styrenic resin foam and method for manufacturing same

    CN105722901A

  • Flame-retardant EPS composite foam containing expandable graphite and preparation method of flame-retardant EPS composite foam

    CN113045336A